Effect of Economic Responsibility on Community Engagement: A Study of Wings to Fly Equity Group Foundation in Nyamira County - Ogendi, Ruth Nyabiage; Kigatiira, Kinya K.; Baya, Sammy Yaah (International Journal of Research in Interdisciplinary Studies, 2024)
This study sought to examine the effect of economic responsibility on community engagement by Wings to Fly Equity Group Foundation in Nyamira County. The study was guided by the stakeholder and Carroll’s Pyramid of Corporate Social Responsibility Model theories. The study used a descriptive research design, and collected data from sample size of 133 participants drawn from the community members who had directly or indirectly benefitted from the program of Wings to Fly in the five sub-counties in Nyamira; Nyamira North, Nyamira South, Borabu, Masaba North, and Manga by Equity in Nyamira County. The data was analysed descriptively and through inferential statistics with findings presented in tables, graphs and charts. The findings revealed a positive correlation between economic responsibility and community engagement. While the community overwhelmingly appreciated the bank's presence and supported its projects, opinions varied on certain aspects of community engagement practices. The conclusions underscored the pivotal role of economic responsibility in shaping positive community engagement. Recommendations included having tailored community engaged strategies, sustainable economic empowerment programs, long-term commitment to CSR and a mandatory CSR reporting Standard.